Corrosion behavior of ZrN coated ferritic/martensitic steel in liquid lead-bismuth eutectic - Changda Zhu; Guiliang Liu; Baohua Yu; Qingsong Chen; Wei Zhang; Jian Yang; Jiuguo Deng; Yilong Zhong; Ning Liu; Jijun Yang (Nuclear Materials and Energy, 2023)
The corrosion resistance of the ZrN coating deposited on ferritic/martensitic (F/M) steel by the magnetron sputtering method was investigated in static liquid lead–bismuth eutectic (LBE) at 450 ∼ 650 °C. After LBE corrosion test, although ZrN was oxidized to form ZrO2, no spallation, dissolution attack and liquid Pb/Bi penetration occurred in the coating. The results indicate that oxidized coatings still have good adhesion and could protect the F/M steels substrates from LBE corrosion. However, several microscopic cracks and voids inside the coating were observed, which was related to the volume expansion induced by Pilling-Bedworth ratio (PBR) effect and phase transformation. Further, the microscopic corrosion mechanism of the coating was discussed.